Atividades de revisão espaçada em metodologias ativas para melhorar a retenção no ensino de matemática para engenharia: um estudo experimental - Salustiano, Acácio Fonseca (2025)
The dropout rate in engineering courses may be associated with the difficulty in assimilating calculus concepts, which compromises the training of qualified professionals. This study investigates the impact of spaced reviews present in active methodologies for teaching Calculus. First, we conducted a Systematic Literature Review (SLR) that analyzed 474 studies, of which only two were selected, highlighting the scarcity of empirical research on the topic. For this reason, we carried out a controlled experiment comparing an experimental group, which underwent spaced reviews within 48 hours, with a control group, which used active methodologies without induced spaced reviews. The results indicated that the experimental group achieved a passing rate of 57.38%, compared to 30.77% in the control group, representing an 86.60% improvement in the passing rate. These findings suggest that combining spaced activities with active methodologies can enhance knowledge retention and academic performance in Calculus instruction.